DAMPAK BELANJA NEGARA TERHADAP TINGKAT KEGIATAN EKONOMI DI INDONESIA - Christine Tambunan; Jakaria Amin (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
This study is to examine and to analyze the impact of State Budget Expenditure on the Level of Economic Activity in Indonesia. Using the Autoregressive-Distributed Lag (ARDL) method. And using data from 2008-2017. The result of this empirical study is that in the long run, state budget expenditure, consisting of Employee Expenditure, Special Allocation Fund (DAK) and General Allocation Fund (DAU,) has a significant positive effect on Level of Economic Activity. On the contrary, Capital Expenditure has a significant negative impact on growth. While Goods Expenditure shows a negative effect, though it was not statistically significant.